Interaction-driven distinctive electronic states of artificial atoms at the ZnO interface. (24th April 2017) - Chakraborty, Tapash; Manaselyan, Aram; Barseghyan, Manuk
Abstract: We have investigated the electronic states of planar quantum dots at the ZnO interface containing a few interacting electrons in an externally applied magnetic field. The electron–electron interaction effects are expected to be much stronger in this case than in traditional semiconductor quantum systems, such as in GaAs or InAs quantum dots. In order to highlight that stronger Coulomb effects in the ZnO quantum dots, we have compared the energy spectra and the magnetization in this system to those of the InAs quantum dots. We have found that in the ZnO quantum dots the signatures of stronger Coulomb interaction manifests in an unique ground state that has very different properties than the corresponding ones in the InAs dot. Our results for the magnetization also exhibits behaviors never before observed in a quantum dot for a realistic set of parameters. We have found a stronger temperature dependence and other unexpected features, such as paramagnetic-like behavior at high temperatures for a quantum-dot helium.